Long-term Effect and Predictive Factors of Motor Cortex and Spinal Cord Stimulation for Chronic Neuropathic Pain - TANEI, Takafumi (Neurol Med Chir (Tokyo), 2018)
The long-term effects of motor cortex stimulation (MCS) and spinal cord stimulation (SCS) remain unknown. To identify the long-term effects after MCS or SCS and determine any associated predictive factors for the outcomes. Fifty patients underwent MCS (n = 15) or SCS (n = 35) for chronic neuropathic pain. The degree of pain was assessed preoperatively, at 1, 6, and 12 months after surgery, and during the time of the last follow-up using Visual Analog Scale (VAS). Percentage of pain relief (PPR) was calculated, with “long-term effect” defined as PPR ≥ 30% and the presence of continued pain relief over 12 months. Outcomes were classified into excellent (PPR ≥ 70%) and good (PPR 30–69%) sub-categories. Long-term effects of MCS and SCS were observed in 53.3% and 57.1% of the patients, respectively. There were no predictive factors of long-term effects identified for any of the various preoperative conditions. However, the VAS at 1 month after surgery was significantly associated with the long-term effects in both MCS and SCS. All patients with an excellent outcome at 1 month after the surgery continued to exhibit these effects. In contrast, patients with the good outcome at 1 month exhibited a significant decrease in the effects at 6 months after surgery. The long-term effects of MCS and SCS were approximately 50% during the more than 8.5 and 3.5 years of follow-up, respectively. The VAS at 1 month after surgery may be a postoperative predictor of the long-term effects for both MCS and SCS.